A numerical study on soot formation in methane-ethanol diffusion flames. (15th November 2022) - Lee, Chia Chun; Tran, Manh-Vu; Tan, Boon Thong; Ooi, Jong Boon; Chong, Cheng Tung; Scribano, Gianfranco
Highlights: Soot volume fraction and particle number density increase with ethanol blending ratio. The degree of soot enhancement decreases with further increase in ethanol blending ratio. Effect of ethanol on soot concentration follows the order: chemical > dilution > thermal. Thermal effect has a dominant influence on the flame temperature, but not on soot. Ethanol addition promotes the HACA pathway and surface growth mechanism. Abstract: Numerical simulation was carried out to investigate the effect of ethanol addition on the soot formation characteristics of methane diffusion flame. The ethanol blending ratio in methane ranged from 0 to 40 % in terms of the carbon contribution, ensuring a constant carbon flow rate for all cases. The sooting diffusion flames were modelled in an open-source environment, OpenFOAM, whereby-two different soot modelling approaches were attempted, including one detailed soot model and one semi-empirical soot model. Numerical results revealed that ethanol addition increased the soot volume fraction; however, further increase in the ethanol blending ratio (>20 %) reduced the relative enhancement of the soot concentration. Decoupling analysis was conducted to study the dilution, thermal, and chemical effects of ethanol separately. It was found that the dilution effect increased with the ethanol blending ratio. Also, the flame temperature was primarily affected by the thermal effect of ethanol. Despite these factors, the chemical effect of ethanol still played a dominant role in increasing soot formation. Analysis of the soot formation pathway revealed that ethanol addition promoted soot formation mainly through the acetylene addition reactions and polycyclic aromatic hydrocarbons (PAHs) addition reactions, which contributed to the hydrogen-abstraction-acetylene-addition (HACA) and surface growth mechanisms, respectively. Soot oxidation was enhanced with ethanol addition, which resulted in greater soot reduction; however, the overall effect of ethanol on soot formation remained positive.